Run-time profiling of Algol 68-R programs using DIDYMUS and SCAMP - Brailsford, David F.; Foxley, E.; Mander, K. C.; Morgan, D. J. (Association for Computing Machinery, 1977)
Information concerning the run-time behaviour of programs ("program profiling") can be of the greatest assistance in improving program efficiency. Two software devices have been developed for use on ICL 1900 Series machines to provide such information.